2005
DOI: 10.1002/pen.20390
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of multimodal vs. bimodal polyethylene pipe resins for PE-100 applications

Abstract: In this paper several high density polyethylene pipe resins are compared to polyethylene resins made in the Phillips Loop-Slurry Process (single-reactor), using a catalyst of chromium on modified aluminophosphate (Cr/AlPO 4 ). A brief description of the Cr/AlPO 4 system is presented along with polymer chain architecture (i.e., topology) and other structural aspects of polymers made from these catalysts. The physical properties of these resins and their fabricated pipe processing/performance properties were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 33 publications
0
57
0
Order By: Relevance
“…The result shows that the high molecular component (UHMWPE) can effectively elevate the viscosity close to zero shear. Previous studies [4] have shown that Newtonian (zero shear) viscosity can successfully be used to model the effects of gravity-induced sag in commercial large-diameter pipe processing and an inverse relationship between zero shear viscosity and gravity-induced sag was found. Therefore, we concluded that with a small amount of UHMWPE, the zero shear viscosities of HDPE/UHMWPE composites could be elevated and the happening of gravity-induced sag during pipe manufacturing may effectively be avoided.…”
Section: Influence Of Uhmwpe On Rheological Propertymentioning
confidence: 89%
See 2 more Smart Citations
“…The result shows that the high molecular component (UHMWPE) can effectively elevate the viscosity close to zero shear. Previous studies [4] have shown that Newtonian (zero shear) viscosity can successfully be used to model the effects of gravity-induced sag in commercial large-diameter pipe processing and an inverse relationship between zero shear viscosity and gravity-induced sag was found. Therefore, we concluded that with a small amount of UHMWPE, the zero shear viscosities of HDPE/UHMWPE composites could be elevated and the happening of gravity-induced sag during pipe manufacturing may effectively be avoided.…”
Section: Influence Of Uhmwpe On Rheological Propertymentioning
confidence: 89%
“…However, compared with unimodal resins, bimodal PE-100 resins lack the melt elasticity due to the absence of both long chain branching (LCB) and the very high molecular weight tail [4]. The result is that PE-100 resins are limited in producing large diameter, thick wall pipes because the molten polymers tend to sag before hardening.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In order to reach higher mechanical properties for specific applications, PE with high molecular weight had been commercialized [7,8]. The main drawback of high molecular weight PE's is their high melt viscosity which limits their processability.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] There is often an advantage to having two or more distinct polymer subpopulations. The production of multimodal polymers is frequently achieved by blending polymers made in separate reactions, [4][5][6] often in separate reactors. [7][8][9] When working with polymers for in vivo applications such as those used for drug delivery, the use of An automatic molecular weight controller is used in semi-batch reactions to produce final polymers that contain distinct subpopulations with different molecular weight distributions (MWD).…”
mentioning
confidence: 99%